Effect of Ananas comosus methanol leaf extract on immature, non-pregnant and pregnant uterus of adult female albino wistar rat - Johnson EI; Ekanem AU; Bassey E; Nwafor P (Ibom Medical Journal)
Background: The leaves of Ananas comosus is used traditionally as an abortifacient among the Indians.